Prospective, Multi-Centre, Single-Arm Study of Mechanical Thrombectomy using Solitaire FR in Acute Ischemic Stroke-STAR - Pereira, Vitor M (2013)
BACKGROUND AND PURPOSE: Mechanical thrombectomy using stent retriever devices have been advocated to increase revascularization in intracranial vessel occlusion. We present the results of a large prospective study on the use of the Solitaire FR in patients with acute ischemic stroke. METHODS: STAR was an international, multicenter, prospective, single-arm study of Solitaire FR thrombectomy in patients with large vessel anterior circulation strokes treated within 8 hours of symptom onset. Strict criteria for site selection were applied. The primary endpoint was the revascularization rate (3TICI 2b) of the occluded vessel as determined by an independent core lab. The secondary endpoint was the rate of good functional outcome (defined as 90-day modified Rankin scale (mRS) 0–2). RESULTS: A total of 202 patients were enrolled across 14 comprehensive stroke centers in Europe, Canada and Australia. The median age was 72 years, 60% were female patients. The median National Institute of Health Stroke Scale (NIHSS) was 17. Most proximal intracranial occlusion was the internal carotid artery in 18%, the middle cerebral artery in 82%. Successful revascularization was achieved in 79.2% of patients. Device and/or procedure related severe adverse events were found in 7.4%. Favorable neurological outcome was found in 57.9%. The mortality rate was 6.9%. Any intracranial hemorrhagic transformation was found in 18.8% of patients, 1.5% were symptomatic. CONCLUSIONS: In this single arm study, treatment with the Solitaire(™) FR device in intracranial anterior circulation occlusions results in high rates of revascularization, low risk of clinically relevant procedural complications, and good clinical outcomes in combination with low mortality at 90 days. CLINICAL TRIAL REGISTRATION: This study is registered with ClinicalTrials.gov, number NCT01327989.